The measurement of crime prevention intensity and its impact on levels of crime - Bowers, Kate (The British journal of criminology, 2004)
Crime prevention activities vary both in the types of intervention that are deployed e.g. target hardening, increased surveillance, offender targeting/diversion and in the levels of activity taking place over time. The latter is best described as the intensity of crime prevention. This paper examines different ways of measuring the intensity of crime prevention schemes and explores the impact of intensity on reducing crime. Scheme intensity can be measured in a variety of ways, including the number of measures installed, the simple cost of the measures, the amount of staff time spent on project implementation and using more complex concepts such as levered-in-costs. Intensity measures can be derived using both input and output data i.e. costs incurred by the project and the number of measures installed, respectively. This paper compares these different measures and deals with issues concerning the identification of relevant populations to produce rates of intensity cost-per-head measures for schemes. These methods have been applied to 21 burglary projects undertaken in the north of England, as part of the Home Office's Reducing Burglary Initiative. The measures are also used to assess the relationship between scheme intensity and scheme effectiveness, measured in terms of number of burglaries reduced. The power of crime prevention intensity in explaining outcomes after other variables have been accounted for is then assessed